Atuação do enfermeiro na rede básica de saúde frente a gestante com infecção do trato urinário - Araujo, Maria Gorete Pereira de (2011)
The Urinary Tract Infection (UTI) in pregnancy is important as a consequence of the high incidence during the gestation. It is the third most common clinical complication in pregnancy affecting 10-12% of women whether prevalence is increasing in the first trimester of pregnancy, it may also contribute to maternal and infant mortality. Due the relevance for the results of obstetric and neonatal complications from UTI, these complications must be prevented, because it can lead to health hazards to pregnant women and newborns, producing a direct effect on morbidity and perinatal mortality. On this basis, it was defined as objectives of this research the identification of the profile of nurses from the Family Health Strategy (FHS) in the East and West Health Districts from the city of Natal / RN before the women with UTI and to verify the nurse performance during prenatal consultations. This is an exploratory study with a quantitative approach using a sample of 40 nurses active workers during this survey, it was approved by the Research Ethics Committee of the Universidade Federal do Rio Grande do Norte Protocol n0 232/10 P-CEP/UFRN and opinion n0 080/2011. The tool for data collection was a structured interview. The data collected were organized into an electronic database application Microsoft ® Excel 2007, exported and analyzed using the Statistical Package for Social Sciences (SPSS) version 17.0, and coded, tabulated and presented through tables and charts into their respective percentage distributions, using the descriptive and inferential statistical analysis, chi-square test and significance level of 5% (distribution in relative and absolute frequencies) in the independent variables. Therefore, it was observed from these results that the longer action of nurses in the FHS from the East and Weast health districts of the city of Natal/RN contributed to the development of a greater number of activities to control the incidence of UTI in women who are attended in the prenatal care service, proven by significance in statistics